2006
DOI: 10.1007/s10295-006-0171-7
|View full text |Cite
|
Sign up to set email alerts
|

Production and characterization of thermostable alkaline phytase from Bacillus laevolacticus isolated from rhizosphere soil

Abstract: Proteases are one of the largest groups of hydrolytic enzymes constituting about 60% of total worldwide sales of industrial enzymes due to their wide applications in detergent, leather, textile, food and pharmaceutical industry. Microbial proteases have been preferred over animal and plant proteases because of their fundamental features and ease in production. Bacillus infantis SKS1, an alkaline protease producing bacteria has been isolated from garden soil of north India and identified using morphological, bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
108
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(121 citation statements)
references
References 38 publications
(56 reference statements)
10
108
1
2
Order By: Relevance
“…But, in several similar studies, it showed that wheat bran and sucrose was the best carbon source for phytase production by some Bacillus sp. [23][24][25], however, it poorly supported phytase production in B. laevolacticus [20]. In this study, fructose, maltose and sucrose also was very effect on production of phytase.…”
Section: Resultsmentioning
confidence: 73%
See 4 more Smart Citations
“…But, in several similar studies, it showed that wheat bran and sucrose was the best carbon source for phytase production by some Bacillus sp. [23][24][25], however, it poorly supported phytase production in B. laevolacticus [20]. In this study, fructose, maltose and sucrose also was very effect on production of phytase.…”
Section: Resultsmentioning
confidence: 73%
“…Various sugars (monosaccharides and disaccharides) have been analyzed, sucrose was able to support maximal phytase expression (0.106 U/ml). Upon combining sucrose and pea flour, the phytase production increased to 0.35 U/ml as compared to 0.299 U/ml when pea flour was the sole carbon source [20]. Nitrogen sources also affected enzyme production.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations